Beyond Survival: Multisystem Life-Threatening Illness in an Infant with Congenital Heart Disease and Sepsis - Windy Oliviany; Rr. Wening Gelar Pratidina; Luhung Sekar Kinanti (Medical and Health Journal, 2026)
Introduction: Congenital malformations are a leading cause of infant disability and mortality. Congenital infections, particularly cytomegalovirus (CMV) and Toxoplasma gondii, are associated with structural abnormalities of multiple organ systems, including congenital heart disease (CHD). In utero infection may disrupt cardiac organogenesis, increasing the risk of heart failure. Infants with CHD are also highly susceptible to sepsis, frequently requiring pediatric intensive care. Managing life-threatening conditions in infants presents significant clinical challenges, including complex therapeutic decisions, drug dosing, and multidisciplinary care. Case Report: A 1-month-old male infant presented with poor feeding and lethargy. He had been previously diagnosed with failure to thrive and CHD consisting of atrial septal defect (ASD) and ventricular septal defect (VSD). Further evaluation revealed heart failure (Ross III), congenital CMV and toxoplasmosis infections, sepsis, bronchopneumonia, prolonged jaundice, and hydrocele dextra. The patient required PICU admission for 6 days followed by 7 days of inpatient care. Clinical improvement was achieved following comprehensive medical management, and the patient was discharged in stable condition. Conclusion: Congenital infections may play a critical role in the development and clinical severity of CHD, contributing to heart failure and increased susceptibility to sepsis. Early recognition and integrated multidisciplinary management are essential to improve outcomes in infants with multiple life-threatening conditions, emphasizing care that extends beyond survival toward functional recovery..